Body of KnowledgeIklan Politik Televisi - Wijaya, Sri Herwindya Baskara (KOMUNITAS, 2014)
Begin campaign general electoral in 1999, world of political in Indonesia came in newÂ  face.Â  ManyÂ  politicalÂ  partyÂ  beginÂ  useÂ  television mediaÂ  toÂ  makeÂ  promotion. However in before general electoral, political party only use some media without televisionÂ  suchÂ  usÂ  newspaper,Â  radioÂ  andÂ  belowÂ  theÂ  lineÂ  media.Â  SoÂ  far,Â  some politicalÂ  partyÂ  haveÂ  usedÂ  televisionÂ  toÂ  advertising political.Â  ThereÂ  areÂ  Partai Demokrat, Partai Golkar, PDIP, PKS, PAN, PKB, PPP, Partai Gerindra, Partai Hanura, etc up to new political party such is Partai Nasdem. Choosing television asÂ  advertisingÂ  mediaÂ  becauseÂ  reasonsÂ  ofÂ  massiveÂ  and moreÂ  âliveâÂ  inÂ  public perception.Â  SoÂ  itÂ  needÂ  exactlyÂ  strategyÂ  toÂ  advertiseÂ  inÂ  televisionÂ  especiallyÂ  see some factor are track and record of political partyor candidate, time, message content, advertising creator, ethic and media distributor. Key words:Political party, political advertising, television